2003
DOI: 10.2214/ajr.181.2.1810367
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Interpretations of After-Hours CT and Sonography by Radiology Residents Versus Final Interpretations by Body Imaging Radiologists at a Level 1 Trauma Center

Abstract: Our evaluation of discrepancy rates was unusual in that we included interpretations of sonograms, on which residents and the attending radiologist had a higher rate of agreement (99.5%). Because of the high agreement in the interpretation of sonograms, the overall discrepancy rate was 3.8%. However, if only body CT scan interpretations were evaluated, our results were closer to the rates reported in previously published studies. Major discrepancies led to a change in patient treatment but did not lead to any i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
59
0
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(70 citation statements)
references
References 15 publications
5
59
0
3
Order By: Relevance
“…These circumstances may well suit certain individuals more than others. Indeed, previous studies comparing resident CT performance have shown very good agreement with experienced specialist radiologists for studies as diverse as abdominal trauma [20], appendicitis [21] and CT pulmonary angiography [22]. Seemingly, the same cannot be assumed for CTC.…”
Section: Discussionmentioning
confidence: 99%
“…These circumstances may well suit certain individuals more than others. Indeed, previous studies comparing resident CT performance have shown very good agreement with experienced specialist radiologists for studies as diverse as abdominal trauma [20], appendicitis [21] and CT pulmonary angiography [22]. Seemingly, the same cannot be assumed for CTC.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] An argument for providing continuous in-house attending coverage is the presence of errors in preliminary interpretation of examinations by residents; however, the error rate for overnight preliminary interpretations by residents has been shown to be quite low. [4][5][6][7][8] CT examination of the head is the most frequently requested after-hours study and can account for up to 57% of all CT examinations performed on call. 9 The fear of being unable to detect intracranial hemorrhage among radiology residents at our institution was the impetus for our study.…”
mentioning
confidence: 99%
“…Differences between initial emergency CT reports by general radiologists or residents and secondary interpretation by specialists revealed discrepancy rates of 6-27% but change in patient management in only 1-5% [10][11][12]. In studies looking at specialist oncological radiology review of external cross-sectional imaging, radiological staging was changed or major disagreements found in 12-19% of patients but actual change in management in only 3-9% [13][14][15].…”
mentioning
confidence: 99%